The negotiation book your definitive guide to successful negotiating - Gates, Steve (Ascent Audio, 2023)
Become the best negotiator you can be, one manageable step at a time In the newly updated third edition of The Negotiation Book: Your Definitive Guide to Successful Negotiating, distinguished commercial negotiator Steve Gates delivers a singular and practical guide to the art and science of negotiation. The book lays out the behaviors and traits associated with successful negotiation and offers a comprehensive model for how power, process, and behavior can have substantial impacts on your next negotiation. You'll also learn how you can shape these factors to optimize value for yourself, your client, or your organization. The author shows you how to secure more agreements and realize more value with every agreement you conclude. Through simple, realistic, and hands-on advice, you'll improve as a negotiator and apply straightforward techniques to the real-world, dynamic environments in which your negotiations take place. You'll also find: strategies for maintaining a balanced perspective and keeping your ego in check; maintaining a focus on the interests and priorities of the other party/parties; and incremental steps for improving your negotiation ability that are easy to apply and retain.
Online resource; title from title details screen (O'Reilly, viewed January 31, 2023)
Keywords: Negotiation in business; Negotiation in business -- Case studies; Négociations (Affaires); Négociations (Affaires); Études de cas; Audiobooks; Case studies; Livres audio; Études de cas